Being patient provides peace - Veneranda, Ntakwasa (Torture Journal, 2018)
When I was still young, my parents used to tell us how our family had been deported by the government from Ruhengeri to Nyamata in 1959, when massacres based on ethnic conflicts happened for the first time in Rwanda. My father also told us that the whole region of Bugesera had been a forest and that there were many animals there. Most of my relatives who had been forced into the forest by the government at that time died due to a sleeping sickness caused by tsetse flies. In 1965, six years after my family had been displaced and forced to live in what is currently known as Bugesera District, I was born.